Elevated atmospheric CO2 does not modify osmotic adjustment to light and drought in the Mediterranean oak Quercus suber L. - Aranda, I=700 1 Puertolas, J.; Pardos, M.; Pardos, J.A.
(En, Es)
ilus., 40 ref.
Keywords: QUERCUS SUBER; ENRIQUECIMIENTO EN GAS CARBONICO; CAMBIO CLIMATICO; DISPONIBILIDAD DEL AGUA; SOMBRA; ESPAÑA